Validação de marcadores moleculares associados ao gene RB-1 em trigo, e relação com a tolerância à germinação na espiga - Pellizzaro, Kelly (2010)
To identify molecular markers linked to the gene that gives the color of the grain in wheat, we used two F2 populations derived from crosses PFAU x CD0666, which secretes a gene for grain color and PFAU x CD0559, segregating for two genes. For the analysis with microsatellite markers was carried out a screening of the parents, to identify polymorphic primers located in regions of localization of genes RA1, RB1 and RD1. In the population PFAU x CD0666 it was analyzed 44 loci, and 38 of them did not show polymorphism. The six polymorphic markers are on chromosome 3A (Xgwm247), 3B (Xbarc229, Xgwm108, Xgwm247 and Xbarc344) and 3D (Xwmc631 and Xbarc323). Mendelian segregation was confirmed by the chi-square (χ2), with the exception of the markers Xgwm108 and Xbarc229 that had a distorted segregation. Linkage analysis between molecular markers and color of the grain was performed with the program GQMOL using the mapping function of Kosambi. The marker Xbarc344 was identified as linked to the gene of color at a distance of 26.1 cM and an efficiency of selection of 83.25%. There was no association of this marker with the tolerance to sprouting and there was no association of grain color with tolerance sprouting. In the population PFAU x CD0559 segregating for two color genes were evaluated 48 molecular markers of linkage groups 3A, 3B and 3C. The Mendelian segregation of polymorphic markers (Xbarc164, Xgwm631 and Xbarc77) was confirmed by the chi-square test. A maximum likelihood function was used to estimate the frequency of recombination, whereas the population segregates for two independent genes for grain color. However, it wasn't detected linkage of any markers for the red color of the wheat grain in this population.